Atomic Mechanisms of Timothy Syndrome-Associated Mutations in Calcium Channel Cav1.2 - Korkosh, Vyacheslav S.; Kiselev, Artem M.; Mikhaylov, Evgeny N.; Kostareva, Anna A.; Zhorov, Boris S. (Frontiers in Physiology, 2019)
Timothy syndrome (TS) is a very rare multisystem disorder almost exclusively associated with mutations G402S and G406R in helix IS6 of Cav1.2. Recently, mutations R518C/H in helix IIS0 of the voltage sensing domain II (VSD-II) were described as a cause of cardiac-only Timothy syndrome. The three mutations are known to decelerate voltage-dependent inactivation (VDI). Here we report a case of cardiac-only Timothy syndrome caused by mutation R518C. To explore possible impact of the three mutations on interdomain contacts, we modeled channel Cav1.2 using as templates Class Ia and Class II cryo-EM structures of presumably inactivated channel Cav1.1. In both models, R518 and several other residues in VSD-II donated H-bonds to the IS6-linked α1-interaction domain (AID). We further employed steered Monte Carlo energy minimizations to move helices S4-S5, S5 and S6 from the inactivated-state positions to those seen in the X-ray structures of the open and closed NavAb channel. In the open-state models, positions of AID and VSD-II were similar to those in Cav1.1. In the closed-state models, AID moved along the β subunit (Cavβ) towards the pore axis and shifted AID-bound VSD-II. In all the models R518 retained strong contacts with AID. Our calculations suggest that conformational changes in VSD-II upon its deactivation would shift AID along Cavβ towards the pore axis. The AID-linked IS6 would bend at flexible G402 and G406, facilitating the activation gate closure. Mutations R518C/H weakened the IIS0-AID contacts and would retard the AID shift. Mutations G406R and G402S stabilized the open state and would resist the pore closure. Several Cav1.2 mutations associated with long QT syndromes are consistent with this proposition. Our results provide a mechanistic rationale for the VDI deceleration caused by TS-associated mutations and suggest targets for further studies of calcium channelopathies.